Pengaruh Agility dan Passion Terhadap Prestasi Belajar Mahasiswa Jurusan Manajemen Universitas Serang Raya - Muhammad Syukron; Hany Azza Umama (Sains: Jurnal Manajemen dan Bisnis, 2020)
This study aims to measure the effect of Agility and Passion on Learning Achievement in Jurusan Management Universitas Serang Raya Banten. Agility problems rarely to research in the field of management, while Passion is still relatively little research done, so researchers are interested in researching with that title. In this study, 83 samples were used and the data were collected using a questionnaire. The data analysis  tool used is Multiple Linear Regression. The result of the study conclude that partially Agility has no significant effect on Learning Achievement, partial Passion has a significant effect on Learning Achievement, while simultaneously Agility and Passion have a significant effect on Learning Achievement. This study develops a model of increasing student Learning Achievement in the face of the industrial revolution 4.0